Preparation method and application of strontium chloride / expanded vermiculite composite ammonia storage material
Patent Information
- Application Number
- CN202611360319.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-30
AI Technical Summary
反复吸附-脱附过程产生的结块与粉碎现象,会逐步削弱SrCl2的吸附-解吸能力,进一步恶化材料循环性能,另一方面也会带来SSCR系统充氨时间长、生产效率低的弊端问题
[0012]本发明在保留氯化锶优异氨吸附特性的基础上,有效提升氯化锶的氨吸附性能,同时解决氯化锶储氨材料在吸附-脱附循环过程中易结块、易粉化结构稳定性差的技术问题。相较于现有技术,本发明具备以下优点:
Smart Images

Figure CN123002872A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of ammonia storage and adsorption materials, specifically relating to a method for preparing a strontium chloride / expanded vermiculite composite ammonia storage material and its application. Background Technology
[0002] With the development of global industrialization, environmental problems caused by air pollution have seriously affected people's quality of life and health. Nitrogen oxides (NOx) x As one of the six key air pollutants, NOx is becoming increasingly important as global emission standards become more stringent. x This has become a long-term goal. Selective catalytic reduction (SCR) systems are used to eliminate NO. x One of the most common methods, in which the NH3-SCR system can remove NO x The reduction of NH3 to water (H2O) and nitrogen (N2) has become a common technique. However, NH3 is a toxic and hazardous gas with an irritating odor. The safe storage, stable transport, and precise release of NH3 in SCR systems directly affect the NO production in the SCR system. x Conversion efficiency and NH3 escape control are crucial factors; therefore, developing efficient NH3 storage and release regulation strategies has become a key issue that urgently needs to be addressed in the practical application of SCR technology.
[0003] In traditional SCR systems, urea ((NH2)2CO) can indirectly supply ammonia through hydrolysis / pyrolysis. Urea-based selective catalytic reduction (Urea-SCR) technology has become a popular choice for vehicle exhaust NO emission control. x The mainstream technology strategy for urea control. However, this technology faces numerous challenges under actual vehicle operating conditions, including the need for high exhaust temperatures for complete urea decomposition, susceptibility to freezing at low temperatures, the potential for pyrolysis byproducts to clog nozzles or pipelines, catalyst poisoning due to urea residues, and the release of CO2 during the decomposition process. Therefore, solid-state selective catalytic reduction (SSCR) technology has become a new generation technology solution to replace the Urea-SCR system.
[0004] In SSCR systems, NH3 is typically complexed with alkaline earth metal halides (AEMH) and stored as ammonia complexes. Due to its excellent NH3 storage capacity, simple addition and preparation process, and good safety, it has become a highly competitive NH3 storage carrier. By directly adding ammonia, the denitrification efficiency of solid-state SCR systems at low exhaust temperatures has been improved. Therefore, researchers have conducted various studies and applications of AEMH as an ammonia carrier, including hydrogen storage and heat pumps. Among these, strontium chloride (SrCl2) exhibits a particularly outstanding theoretical ammonia storage capacity; 1 mol of SrCl2 can complex 8 mol of NH3 to form Sr(NH3)8Cl2, and controllable ammonia desorption can be achieved at medium and low temperatures. Throughout the process, it is used solely as a carrier without significant mass loss, demonstrating significant advantages in ammonia storage and on-demand release in automotive SCR systems.
[0005] However, pure SrCl2 as an ammonia carrier has serious structural defects in applications. After complete ammoniation, its volume expands up to four times, and its porosity increases significantly to about 70%, easily leading to the breakage and pulverization of the molded material. During long-term ammonia adsorption-desorption cycles, the material can also agglomerate, melt, or even volatilize and be lost, causing a decline in its cycle performance. The agglomeration and pulverization caused by repeated adsorption-desorption processes gradually weaken the adsorption-desorption capacity of SrCl2, further deteriorating the material's cycle performance. On the other hand, it also brings the disadvantages of long ammonia charging time and low production efficiency to the SSCR system. More importantly, pulverized particles also increase the risk of blockage in vehicle pipelines, directly threatening the safe and stable operation of the vehicle system. These problems seriously hinder the promotion and application of this material. Summary of the Invention
[0006] The main objective of this invention is to provide a method for preparing strontium chloride / expanded vermiculite composite ammonia storage material and its application, so as to overcome the shortcomings of the prior art.
[0007] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: The first aspect of the present invention provides a method for preparing a strontium chloride / expanded vermiculite composite ammonia storage material, comprising: Provide expanded vermiculite materials with multi-level pore structure; Expanded vermiculite was mixed and stirred with strontium chloride aqueous solution to obtain a mixed slurry, which was then allowed to stand and age. The mixed slurry was dried to obtain the strontium chloride / expanded vermiculite composite ammonia storage material.
[0008] A second aspect of the present invention provides a strontium chloride / expanded vermiculite composite ammonia storage material, which is prepared by the aforementioned method for preparing strontium chloride / expanded vermiculite composite ammonia storage material. The strontium chloride / expanded vermiculite composite ammonia storage material comprises: an expanded vermiculite matrix having a multi-level porous structure as a carrier, and strontium chloride, an active adsorbent component uniformly loaded on the expanded vermiculite matrix.
[0009] A third aspect of the present invention provides the use of the aforementioned strontium chloride / expanded vermiculite composite ammonia storage material in an on-board solid ammonia SCR system.
[0010] A fourth aspect of the present invention provides an ammonia storage material for SCR denitrification of motor vehicle exhaust, the ammonia storage material comprising the aforementioned strontium chloride / expanded vermiculite composite ammonia storage material.
[0011] The fifth aspect of the present invention provides a method for controlling NO in motor vehicle exhaust. x The removal method involves placing the aforementioned strontium chloride / expanded vermiculite composite ammonia storage material, after adsorbing ammonia gas, into the exhaust gas passage of a motor vehicle. Under catalytic and reaction temperature conditions, the ammonia gas released by the material reacts with NO in the exhaust gas. x A reduction reaction occurs, completing the removal of NO from the exhaust gas. x Effective removal.
[0012] This invention, while retaining the excellent ammonia adsorption characteristics of strontium chloride, effectively improves its ammonia adsorption performance and simultaneously solves the technical problems of poor structural stability, such as easy agglomeration and pulverization, in strontium chloride ammonia storage materials during adsorption-desorption cycles. Compared with existing technologies, this invention has the following advantages: 1. The raw materials are inexpensive and readily available, resulting in good overall economic efficiency. This invention uses natural primary vermiculite to prepare expanded vermiculite carriers through high-temperature heat treatment. The raw materials are abundant and have low acquisition costs. Compared with existing high-cost carrier materials such as expanded graphite, graphene, and molecular sieves, this invention significantly reduces the preparation cost of composite materials and has good industrial application value.
[0013] 2. Utilizing a multi-level porous framework structure, the material's structural stability is significantly improved, and agglomeration and pulverization are suppressed. Expanded vermiculite possesses a high pore capacity and a structurally stable lamellar layered framework structure. After strontium chloride is uniformly loaded onto the pores and framework surface of expanded vermiculite, the volume deformation during the adsorption and deamination of strontium chloride can be effectively constrained by the support and confinement effect of the rigid framework of the carrier, preventing the agglomeration, clumping, and pulverization of active salt. At the same time, its abundant pore structure provides unobstructed mass transfer channels for ammonia diffusion, fundamentally improving the defects of traditional metal chlorides, such as limited mass transfer and poor cycle stability.
[0014] 3. Achieving a synergistic improvement in ammonia charging rate and ammonia charging capacity, resulting in ammonia storage performance significantly superior to existing conventional materials. Existing physically modified ammonia storage materials generally suffer from slow ammonia charging rates, low ammonia charging efficiency, and mutually restrictive performance parameters, with ammonia charging equilibrium time exceeding 24 hours and an ammonia mass fraction of less than 85%. This invention significantly optimizes ammonia mass transfer efficiency through the synergistic adsorption effect of expanded vermiculite porous structure and strontium chloride. The composite material can achieve an effective ammonia charging efficiency of over 85% within 7 hours, simultaneously improving both the ammonia charging rate and ammonia storage capacity, thus overcoming the bottleneck of existing technologies that struggle to achieve a balance between performance. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the preparation method of the present invention. Detailed Implementation
[0016] To address the technical bottlenecks of limited mass transfer and easy agglomeration in the adsorption of ammonia by metal chlorides, numerous studies have widely adopted the modification approach of loading metal chlorides onto mesoporous supports to construct composite adsorbent materials. These composite materials can synergistically utilize both physical adsorption and chemical complexation, effectively improving and enhancing the ammonia mass transfer performance within metal chloride-based ammonia adsorbents, thereby significantly suppressing agglomeration during adsorption. Some studies have investigated four metal chloride-silicon-supported composite adsorbents using fixed-bed adsorption methods. Ammonia adsorption experiments have confirmed that silicon can significantly improve the ammonia adsorption capacity of metal chlorides. Silicon acts as a skeletal support in metal chloride particles, preventing particle aggregation and increasing the number of pores on the particle surface, which facilitates the diffusion of ammonia into the particles for adsorption. Some studies have constructed SrCl2-carbon nanofiber composites (SrCs) from SrCl2 through electrospinning and a subsequent three-step carbonization process. These materials can support up to 90 wt.% SrCl2 and exhibit a significant and stable ammonia adsorption capacity of 671 mg / g over four ammonia adsorption cycles. The adsorption process maintains good mechanical integrity and exhibits desorption kinetics that are four times faster than SrCl2 powder. Other studies have designed a novel adsorbent using low-cost and structurally stable porous magnesium oxychloride cement as a carrier, combined with SrCl2, achieving an ammonia adsorption capacity as high as 38.01 mmol·g. -1Furthermore, the structure remained intact after 10 ammonia adsorption / desorption cycles, providing theoretical support for further purification and optimized design of the adsorbent. Some studies reported a structurally stable and robust porous SrCl2 composite material supported by graphene oxide (rGO) prepared by cryogenic casting. This material effectively adapts to the volume changes during ammonia adsorption-desorption, exhibiting rapid adsorption-desorption kinetics. This research provides a new approach for the construction of solid ammonia supports in SCR systems and hydrogen storage. Other studies, through loading MgCl2 onto activated carbon and conducting high-pressure adsorption and experimental investigations, found that adsorption-desorption equilibrium could be achieved at a MgCl2 loading of 4 wt.% and an operating temperature of 40 °C. The material maintained high adsorption capacity throughout 15 adsorption-desorption cycles. This adsorbent provides a new approach for ammonia removal and enrichment in industrial pressure swing adsorption hydrogen extraction processes. Some studies have shown that combining CaCl2 with mesoporous silica gel can effectively prevent the decline in mass transfer performance caused by agglomeration. Other studies have reported a method of mixing fine-grained CaCl2 with expanded graphite, which can improve the reaction rate of chemical heat pumps. Some studies have synthesized novel composite adsorbent materials and determined the isohyetal results of ammonia adsorption by the novel composite adsorbent materials CaCl2 / γ-Al2O3 and CaCl2 / vermiculite. The results show that salt modification of the matrix significantly increases the formation of CaCl2×nNH3 complexes, thus significantly increasing the ammonia absorption capacity of the matrix. Some studies have used self-made porous hollow mesoporous silica microspheres (HMSS) as a carrier to support metal halides (MgCl2) as adsorbents, confirming that metal chlorides are the active centers for forming ammonia complexes. When the loading reaches 80 wt.%, the composite material exhibits the optimal ammonia adsorption capacity. Some studies experimentally demonstrated superior cooling performance of solidified composite reaction beds impregnated with expanded graphite and CaCl2 at different evaporation and heat sink temperatures. Other studies prepared three novel composite materials—BaCl2 / vermiculite, BaCl2 / γ-Al2O3, and BaCl2 / (carbon)—using a barium chloride impregnation method, and investigated their performance as ammonia adsorbents. The coefficient of performance (COP) of the composite BaCl2 / vermiculite reached 0.6 for ammonia adsorption in ice-making and air conditioning cycles. Still other studies used calcium chloride (CaCl2) impregnated type A zeolite and strontium chloride (SrCl2) impregnated type A and type X zeolite composite particles as adsorbents, investigating their adsorption performance in automotive selective catalytic reduction systems. These studies revealed that the composite particles exhibited rapid ammonia adsorption kinetics, with rapid physical adsorption from the zeolite reducing ammonia loading and release time, while the chemisorption of CaCl2 / SrCl2 provided abundant ammonia capacity. Furthermore, by optimizing the SrCl2 loading, the composite particles maintain their particle form after the ammonia adsorption-desorption cycle, with a breakage load of 17 N / particle. This structurally stable composite adsorbent provides an opportunity for rapid ammonia loading / release in automotive selective catalytic reduction systems.
[0017] Existing technologies disclose the use of physical mixtures of alkaline earth metal salts and other additives for the synthesis of ammonia storage materials. These materials typically have an effective ammonia charging time exceeding 24 hours, with an ammonia charging mass percentage not exceeding 85%. Furthermore, simultaneously reducing the effective charging time and increasing the ammonia charging mass percentage is difficult to achieve with existing ammonia storage materials. In contrast, researchers have prepared strontium chloride composite adsorbents by modifying carriers such as silica gel, expanded graphite, graphene, and molecular sieves. These materials synergistically enhance the ammonia adsorption performance, thermal conductivity, and adsorption-desorption cycle stability of the composite material through physical adsorption and chemical complexation. When applied to vehicle-mounted SSCR systems, they can achieve rapid heating and accelerate the NH3 desorption rate, ensuring timely NH3 release. However, in industrial-scale promotion and actual vehicle operating conditions, the raw material cost of the adsorbent, the complexity of the preparation process, and large-scale application remain the core bottlenecks restricting the technology's practical application. The high cost of carrier raw materials such as expanded graphite, graphene, and molecular sieves makes them difficult to adapt to the low-cost requirements of industrial mass production, limiting their engineering value. Existing high-performance carrier raw materials are expensive, some preparation processes are complex and demanding, and large-scale production is difficult, resulting in high costs for industrial applications. Currently, most composite materials have long ammonia-charging equilibrium times, and it is difficult to synergistically improve the ammonia-charging rate and capacity. Composite materials cannot adequately suppress the dramatic volume expansion of SrCl2 during ammonia adsorption-desorption, and are prone to agglomeration, pulverization, and loss of active components during cycling, leading to insufficient cycle durability. Powdered particles can also cause safety hazards such as blockage of onboard pipelines, making it difficult to meet the practical requirements for long-term stable operation of onboard solid-state ammonia SCR systems. Therefore, developing low-cost, highly practical composite-based modified strontium chloride materials has become a core research focus.
[0018] Currently, most composite ammonia storage materials use expanded graphite, graphene, molecular sieves, etc. as carrier components. The raw materials for these high-performance carriers are expensive. Some modified systems also require complex processes such as electrospinning, cryogenic casting, multi-step carbonization, and strong acid and alkali modification pretreatment. The preparation process is cumbersome, has high requirements for equipment conditions, poor process reproducibility, and is difficult to scale up production. The overall manufacturing cost remains high, making it difficult to meet the economic requirements for industrial promotion and application and actual vehicle operation conditions, thus restricting the industrialization of this type of ammonia storage technology.
[0019] Most existing materials have an ammonia charging equilibrium time of over 24 hours, and the saturated ammonia mass fraction is usually no more than 85%. Furthermore, there is a significant mutual constraint between the ammonia charging rate and the ammonia charging capacity, making it difficult to simultaneously increase both. Under cyclic conditions, active salt particles are prone to loss and aggregation, and the confinement effect of the carrier skeleton cannot be fully utilized, resulting in limited improvement in the material's cycling performance.
[0020] Even though some literature reports that composite materials exhibit excellent initial adsorption performance under small laboratory sample conditions, it is still difficult to completely solve the inherent problem of volume expansion during the SrCl2 ammoniation-desorption process. During repeated ammonia adsorption-desorption cycles, phenomena such as material agglomeration, pulverization, and loss due to active salt melting and volatilization still occur, causing a continuous decline in adsorption-desorption performance. Pulverized fine particles increase the risk of blockage in on-board pipelines, threatening the safe operation of the entire solid ammonia supply system. Many modification schemes sacrifice loading capacity or increase preparation costs in exchange for cycle stability, failing to simultaneously meet the comprehensive on-board requirements of high ammonia storage performance, simple preparation process, inexpensive raw materials, and long-cycle service.
[0021] In view of the above-mentioned deficiencies in the prior art, the inventors of this application, through long-term research and practice, have come up with the technical solution of this application, which will be explained in detail below.
[0022] Some embodiments of this application provide a method for preparing a strontium chloride / expanded vermiculite composite ammonia storage material, including: An expanded vermiculite with a hierarchical pore structure is provided; the hierarchical pores are mainly mesopores containing a small number of micropores and intergranular macropores, wherein the micropore diameter ranges from 0.4 to 2 nm, the mesopore diameter ranges from 2 to 50 nm with the most probable pore diameter being 3 to 5 nm, and the intergranular macropore diameter is 50 to 80 nm; the micropore volume of the expanded vermiculite is 0.0001 to 0.0002 cm³ / g. -1 The mesoporous volume is 0.0138~0.0157 cm³.g -1 The total pore volume is 0.00143~0.0165 cm³.g -1 ; Expanded vermiculite is mixed and stirred with strontium chloride aqueous solution to obtain a mixed slurry, which is then allowed to stand for aging. The amount of strontium chloride aqueous solution used is based on completely submerging the expanded vermiculite and ensuring uniform impregnation, and there is no special limitation. The solution concentration can be adjusted according to the target loading, preferably 0.02~0.1g / ml.
[0023] The mixed slurry was dried to obtain a strontium chloride / expanded vermiculite composite ammonia storage material.
[0024] In one embodiment, the preparation steps of the expanded vermiculite include: Expansion vermiculite material is obtained by heating raw vermiculite in a muffle furnace to a preset temperature, holding it at that temperature for a preset time, and then allowing it to cool naturally.
[0025] In one embodiment, the preparation method includes: An appropriate amount of strontium chloride was dissolved in deionized water to prepare a strontium chloride aqueous solution. Then, according to a predetermined mass ratio of expanded vermiculite to strontium chloride, expanded vermiculite was weighed and added to the strontium chloride aqueous solution. The mixture was then stirred at a certain stirring rate to prepare a mixed slurry. The prepared slurry was allowed to stand at room temperature for a predetermined time. Finally, the mixed slurry was placed in an electrically heated forced-air drying oven to completely remove moisture. After drying, it was cooled to room temperature and then sealed for storage.
[0026] This scheme uses a solution impregnation method to achieve uniform loading of strontium chloride in the pores of expanded vermiculite. The overall process conditions are mild and the operation is simple. No complex modification process is required, and it is easy to scale up for industrial production. The main process includes high-temperature expansion pretreatment of vermiculite, strontium chloride solution impregnation, and drying.
[0027] In one embodiment, the preset temperature is 800℃-1200℃.
[0028] In one embodiment, the heat preservation time is 30 min to 240 min.
[0029] In one embodiment, the mass ratio of the expanded vermiculite to the strontium chloride contained in the strontium chloride aqueous solution is 0.5:10-3.5:10.
[0030] In one embodiment, the static aging time is 20-100 minutes.
[0031] This application proposes a SrCl 2 / A method for preparing expanded vermiculite (EVMT) composite materials. This method innovatively uses a simple and controllable solution impregnation method to uniformly load the active adsorbent component SrCl2 onto a low-cost expanded vermiculite matrix with a hierarchical porous structure. Expanded vermiculite can be used as a carrier by high-temperature thermal expansion treatment of natural vermiculite, which is simple to process and significantly reduces the raw material cost and scale-up production threshold of composite materials. At the same time, the solution impregnation operation conditions are mild and the process is simple, making it easy to achieve large-scale production and possessing good industrial production potential. Utilizing the pore confinement effect of expanded vermiculite, the SrCl2-EVMT composite material effectively improves NH3 adsorption efficiency, significantly improves the structural damage problem in the SrCl2 cycle process, enhances the stability of ammonia adsorption-desorption cycle, and alleviates the problems of pulverization, agglomeration, and volatilization loss in the pure salt system cycle. The comprehensive performance of this composite material can meet the actual operating requirements of on-board solid ammonia SCR systems, providing a reliable ammonia source for vehicle exhaust purification, and has good application prospects and economic benefits.
[0032] Some embodiments of this application provide a strontium chloride / expanded vermiculite composite ammonia storage material, which is prepared by the aforementioned method for preparing strontium chloride / expanded vermiculite composite ammonia storage materials. The strontium chloride / expanded vermiculite composite ammonia storage material comprises: an expanded vermiculite matrix with a hierarchical porous structure serving as a carrier, and strontium chloride, an active adsorbent component uniformly loaded onto the expanded vermiculite matrix. This SrCl2 / EVMT ammonia adsorption composite material product uses low-cost, hierarchical porous expanded vermiculite as a carrier, with the strontium chloride active component loaded within the expanded vermiculite pores. The confinement effect of the expanded vermiculite pores mitigates the severe volume expansion during the SrCl2 ammoniation-desorption process, inhibiting material agglomeration, pulverization, and active salt volatilization and loss, thereby improving ammonia adsorption efficiency and cycle stability.
[0033] Some embodiments of this application provide the use of the aforementioned strontium chloride / expanded vermiculite composite ammonia storage material in vehicle-mounted solid ammonia SCR systems.
[0034] Some embodiments of this application provide a method for emitting NO from motor vehicle exhaust. x Adsorption materials include the aforementioned strontium chloride / expanded vermiculite composite ammonia storage material.
[0035] Some embodiments of this application provide a method for detecting NO in motor vehicle exhaust. x The removal method involves bringing the aforementioned strontium chloride / expanded vermiculite composite ammonia storage material into contact with vehicle exhaust gas and adsorbing the NO therein. x .
[0036] The present application will be described in detail below with reference to specific embodiments. However, the implementation of the present application is not limited thereto. Obviously, the embodiments described below are only some embodiments of the present application. For those skilled in the art, other similar embodiments can be obtained without creative effort and all fall within the protection scope of the present application.
[0037] Unless otherwise specified, the raw materials used in the following embodiments can be obtained from the market or made in-house from references, and the production equipment, testing equipment and testing methods used can also be common equipment or methods in the field.
[0038] Example 1 a. Place raw vermiculite in a muffle furnace and heat it to 800°C, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. The strontium chloride solution is prepared by dissolving strontium chloride in deionized water. The concentration of the strontium chloride aqueous solution can be adjusted according to the target loading. The amount of solution used should be sufficient to completely submerge the expanded vermiculite and ensure uniform impregnation, without any special limitation. c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0039] The obtained composite material was placed in a fixed-bed reactor, and its ammonia adsorption capacity was tested. The ammonia adsorption amount was obtained by measuring the mass change of the adsorbent material before and after ammonia adsorption, and the adsorption efficiency of the composite material was determined based on the adsorption amount.
[0040] Adsorption capacity calculation formula: The unit is mmol. . g -1 Note: All experiments were conducted under laboratory conditions. Due to the small amount of adsorbent used, the samples were placed in glass containers for easy collection. The mass of each group of adsorbent samples was 1.5 ± 0.1 g, with slight mass variations between batches.
[0041] Formula for calculating the percentage of ammonia charge by mass: The unit is: % The theoretical ammonia adsorption capacity of strontium chloride is 50.47 (see literature: "Porous Strontium Chloride Scaffolded by Graphene Networks as Ammonia Carriers", DOI:10.1002 / adfm.202008505).
[0042] The test results of two parallel samples in Example 1 are as follows: Group I: Mass before ammonia absorption: 55.4738g; Mass after ammonia absorption: 56.6127g; madsorbent = 1.4915g Group II: Mass before ammonia absorption: 49.7035g; Mass after ammonia absorption: 50.8557g; madsorbent = 1.5074g Qe.1 = 44.9173 mmol . g -1 Qe.2 = 44.9625 mmol . g -1 Qe ,均 =44.9399 mmol . g -1 =89% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 89%.
[0043] Example 2 a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0044] The test results of two parallel samples in Example 2 are as follows: Group I: Mass before ammonia absorption: 51.8035g; Mass after ammonia absorption: 53.0268g; madsorbent = 1.5012g Group II: Mass before ammonia absorption: 54.9351g; Mass after ammonia absorption: 56.1588g; madsorbent = 1.5035g Qe.1 = 47.9342 mmol . g -1 Qe.2 = 47.8765 mmol . g -1 Qe ,均 =47.9054 mmol . g -1 =95% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 95%.
[0045] Example 3 a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 30 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 60 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0046] The test results of two parallel samples in Example 3 are as follows: Group I: Mass before ammonia absorption: 49.7014 g; Mass after ammonia absorption: 50.8848 g; madsorbent = 1.5089 g Group II: Mass before ammonia absorption: 55.6681g; Mass after ammonia absorption: 56.8615g; madsorbent = 1.5006g Qe.1 = 46.1341 mmol . g -1 Qe.2 = 46.7812 mmol . g -1 Qe ,均 =46.4577mmol . g -1 =92% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 92%.
[0047] Example 4 a. Place raw vermiculite in a muffle furnace and heat it to 1200℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 40 min; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0048] The test results of two parallel samples in Example 4 are as follows: Group I: Mass before ammonia absorption: 49.8414 g; Mass after ammonia absorption: 50.9725 g; madsorbent = 1.4967 g Group II: Mass before ammonia absorption: 53.7914g; Mass after ammonia absorption: 54.9459g; madsorbent = 1.5035g Qe.1 = 44.4547 mmol . g -1 Qe.2 = 45.1691 mmol . g -1 Qe ,均 =45.3119mmol . g -1 =90% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours and the ammonia charging mass percentage was 90%.
[0049] Example 5 a. Place raw vermiculite in a muffle furnace and heat it to 900°C, then hold it at that temperature for 120 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 3:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 100 min; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0050] The test results of two parallel samples in Example 5 are as follows: Group I: Mass before ammonia absorption: 49.7102g; Mass after ammonia absorption: 50.8612g; madsorbent = 1.5016g Group II: Mass before ammonia absorption: 57.7914g; Mass after ammonia absorption: 58.9509g; madsorbent = 1.5034g Qe.1 = 45.7590 mmol . g -1 Qe.2 = 45.3678 mmol . g -1 Qe ,均 =45.5634mmol . g-1 =90% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours and the ammonia charging mass percentage was 90%.
[0051] Example 6 a. Raw vermiculite is heated to 1100℃ in a muffle furnace and held at that temperature for 240 minutes, then allowed to cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 3:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 20 min; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0052] The test results of two parallel samples in Example 6 are as follows: Group I: Mass before ammonia absorption: 60.0164 g; Mass after ammonia absorption: 61.1722 g; madsorbent = 1.4885 g Group II: Mass before ammonia absorption: 54.8143g; Mass after ammonia absorption: 55.9556g; madsorbent = 1.4862g Qe.1 = 45.6756 mmol . g -1 Qe.2 = 45.1724 mmol . g -1 Qe ,均 =45.424mmol . g -1 =90% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours and the ammonia charging mass percentage was 90%.
[0053] Example 7 a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then hold it at that temperature for 180 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 2:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 80 min; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0054] The test results of two parallel samples in Example 7 are as follows: Group I: Mass before ammonia absorption: 60.3071 g; Mass after ammonia absorption: 61.4939 g; madsorbent = 1.508 g Group II: Mass before ammonia absorption: 58.8267g; Mass after ammonia absorption: 60.0183g; madsorbent = 1.5042g Qe.1 = 46.2943 mmol . g -1 Qe.2 = 46.5989 mmol . g -1 Qe ,均 =46.4466mmol . g -1 =92% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 92%.
[0055] Example 8 a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 0.5:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry; d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0056] The test results of two parallel samples in Example 8 are as follows: Group I: Mass before ammonia absorption: 52.5008g; Mass after ammonia absorption: 53.6892g; madsorbent = 1.5087g Group II: Mass before ammonia absorption: 55.3864 g; Mass after ammonia absorption: 56.5812 g; madsorbent = 1.5032 g Qe.1=46.3351mmol.g-1Qe.2=46.7551mmol.g-1Qe, both=46.5451 mmol.g-1 =93% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 93%.
[0057] Example 9 a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then hold it at that temperature for 180 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 3.5:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry; d. Allow the slurry obtained in step c to stand and age at room temperature for 80 min; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0058] Example 9: The test results for two parallel samples are as follows: Group I: Mass before ammonia absorption: 52.3768 g; Mass after ammonia absorption: 53.5118 g; madsorbent = 1.50 g Group II: Mass before ammonia absorption: 58.9187g; Mass after ammonia absorption: 57.7661g; madsorbent = 1.5037g Qe.1 = 44.2414 mmol . g -1 Qe.2 = 45.0888 mmol . g -1 Qe ,均 =44.6651mmol . g -1 =89% The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 89%.
[0059] Comparative Example 1: Strontium chloride was loaded onto native vermiculite as a carrier. a. Using untreated, untreated vermiculite to directly load strontium chloride; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add the raw vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of raw vermiculite to strontium chloride of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry; d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / native vermiculite composite material.
[0060] The test results of the two parallel samples in Comparative Example 1 are as follows: Group I: Mass before ammonia absorption: 56.2267g; Mass after ammonia absorption: 57.3786g; madsorbent = 1.5012g Group II: Mass before ammonia absorption: 51.6708g; Mass after ammonia absorption: 52.8123g; madsorbent = 1.5022g Qe.1=45.1364 mmol.g-1Qe.2=44.6991mmol.g-1Qe ,均 =44.9178 mmol·g⁻¹ =89% The strontium chloride / primary vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 89%. The primary vermiculite sheets were tightly stacked with extremely underdeveloped pores, lacking mass transfer channels and adsorption sites for ammonia diffusion, resulting in low ammonia adsorption capacity and low ammonia charging mass percentage.
[0061] Comparative Example 2: Raw vermiculite treated with high-temperature thermal expansion at 1300℃ (exceeding the upper limit of the parameters of this invention). a. Place raw vermiculite in a muffle furnace and heat it to 1300℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0062] The test results of the two parallel samples in Comparative Example 2 are as follows: Group I: Mass before ammonia absorption: 53.8301g; Mass after ammonia absorption: 54.9559g; madsorbent = 1.4982g Group II: Mass before ammonia absorption: 56.6258g; Mass after ammonia absorption: 57.7346g; madsorbent = 1.4956g Qe.1=44.2021mmol.g-1Qe.2=43.6103mmol.g-1Qe ,均 =43.9062 mmol·g⁻¹ =87% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 87%. The vermiculite underwent excessive expansion, and the lamellar layers sintered and collapsed, resulting in a decrease in effective porosity and specific surface area.
[0063] Comparative Example 3: The heat treatment holding time was set to 20 minutes (lower than the lower limit of the parameters of this invention). a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 20 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0064] The test results of the two parallel samples in Comparative Example 3 are as follows: Group I: Mass before ammonia absorption: 51.5346g; Mass after ammonia absorption: 52.6589g; madsorbent = 1.5078g Group II: Mass before ammonia absorption: 52.9869g; Mass after ammonia absorption: 54.0796g; madsorbent = 1.4969g Qe.1=43.8621 mmol.g-1Qe.2=42.9397mmol.g-1Q e,均 =43.4009 mmol·g⁻¹ =86% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia mass percentage was 86%. The vermiculite expansion was insufficient, the interlayer moisture removal was incomplete, the specific surface area and pore volume were insufficient, and the ammonia mass transfer resistance was high.
[0065] Comparative Example 4: The heat treatment holding time was 300 min (exceeding the upper limit of the parameters of this invention). a. Raw vermiculite is heated to 1000℃ in a muffle furnace and held at that temperature for 300 minutes, then allowed to cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0066] The test results of the two parallel samples in Comparative Example 4 are as follows: Group I: Mass before ammonia absorption: 52.4116g; Mass after ammonia absorption: 53.5174g; madsorbent = 1.4931g Group II: Mass before ammonia absorption: 57.5116g; Mass after ammonia absorption: 58.6364g; madsorbent = 1.4959g Qe.1=43.5651 mmol.g-1Qe.2=44.2307mmol.g-1Q e,均 =43.8979 mmol·g⁻¹ =87% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 87%. When vermiculite sheets are exposed to a high-temperature environment for a long time, the structural stability decreases, and pore sintering and structural damage occur, reducing the number of effective adsorption sites.
[0067] Comparative Example 5: The mass ratio of SrCl2 / EVMT was set to 10:5 (EVMT carrier ratio was too high). a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 5:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry; d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0068] The test results of the two parallel samples in Comparative Example 5 are as follows: Group I: Mass before ammonia absorption: 52.5938g; Mass after ammonia absorption: 53.6538g; madsorbent = 1.4987g Group II: Mass before ammonia absorption: 58.8727g; Mass after ammonia absorption: 59.9512g; madsorbent = 1.5045g Qe.1=41.6036 mmol.g-1Qe.2=42.1776mmol.g-1Q e,均 =41.8906 mmol·g⁻¹ =83% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured using the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 83%. The proportion of strontium chloride active component per unit mass of material decreased significantly, and the total number of chemical adsorption active sites was insufficient. Although the mass transfer channels were sufficient, the overall ammonia storage capacity was limited, and the ammonia charging mass percentage was significantly reduced. At the same time, the decrease in active site density also prolonged the effective ammonia charging time to some extent.
[0069] Comparative Example 6: The settling and aging time was 10 minutes. a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 10 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0070] The test results of the two parallel samples in Comparative Example 6 are as follows: Group I: Mass before ammonia absorption: 54.4034g; Mass after ammonia absorption: 55.5328g; madsorbent = 1.5063g Group II: Mass before ammonia absorption: 56.6902g; Mass after ammonia absorption: 57.7853g; madsorbent = 1.4919g Qe.1=44.1028 mmol.g-1Qe.2=43.715mmol.g-1Q e,均 =43.9089 mmol·g⁻¹ =87% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia mass percentage was 87%. Strontium chloride failed to fully enter the vermiculite channels and interlayer gaps, resulting in uneven loading of active components, insufficient loading, and a limited number of effective adsorption sites.
[0071] Comparative Example 7: The settling time was 120 minutes. a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 1:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 120 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0072] The test results of the two parallel samples in Comparative Example 7 are as follows: Group I: Mass before ammonia absorption: 52.2731g; Mass after ammonia absorption: 53.3519g; madsorbent = 1.5072g Group II: Mass before ammonia absorption: 55.8595g; Mass after ammonia absorption: 56.9489g; madsorbent = 1.5013g Qe.1=42.1037 mmol.g-1Qe.2=42.6868 mmol.g-1Q e,均 =42.3953 mmol·g⁻¹ =84% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia mass percentage was 84%. Excessive accumulation of reactive components and blockage of pores led to a decrease in material porosity and specific surface area, and an increase in ammonia mass transfer resistance.
[0073] Comparative Example 8: The mass ratio of SrCl2 / EVMT was set to 10:4 (EVMT carrier ratio was too high). a. Place raw vermiculite in a muffle furnace and heat it to 1000℃, then keep it at that temperature for 60 minutes, and then let it cool naturally to obtain expanded vermiculite material; b. Prepare a strontium chloride solution by dissolving strontium chloride in deionized water; c. Add expanded vermiculite to the strontium chloride aqueous solution prepared in step b at a mass ratio of 4:10, and then stir at a stirring rate of 200 r / min to obtain a mixed slurry. d. Allow the slurry obtained in step c to stand and age at room temperature for 40 minutes; e. Place the composite material that has been left to stand and age in a drying oven to completely remove moisture; f. Cool to room temperature to obtain the strontium chloride / expanded vermiculite composite material.
[0074] The strontium chloride / expanded vermiculite composite material prepared in this embodiment was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 86%.
[0075] The test results of the two parallel samples in Comparative Example 8 are as follows: Group I: Mass before ammonia absorption: 64.109 g; Mass after ammonia absorption: 65.1965 g; madsorbent = 1.4953 g Group II: Mass before ammonia absorption: 50.8218g; Mass after ammonia absorption: 51.9428g; madsorbent = 1.5014g Qe.1=42.7811 mmol.g-1Qe.2=43.9198 mmol.g-1Q e,均 =43.3505 mmol·g⁻¹ =86% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 86%.
[0076] Comparative Example 9: Pure Strontium Chloride Material In this comparative example, expanded vermiculite (i.e., SrCl2 / EVMT mass ratio 0:10) was not added, and strontium chloride aqueous solution was used directly as the control slurry for the mixed slurry; other parameters were the same as in Example 2.
[0077] The test results of the two parallel samples in Comparative Example 9 are as follows: Group I: Mass before ammonia absorption: 49.7951 g; Mass after ammonia absorption: 50.9235 g; madsorbent = 1.4989 g Group II: Mass before ammonia absorption: 53.7814g; Mass after ammonia absorption: 54.9112g; madsorbent = 1.4920g Qe.1=44.2835mmol.g-1Qe.2=44.5434mmol.g-1Q e,均 =44.4135 mmol·g⁻¹ =88% The strontium chloride / expanded vermiculite composite material prepared in this comparative example was used to adsorb ammonia. The adsorption efficiency of ammonia was measured by the adsorption mass difference. The effective ammonia charging time was 7 hours, and the ammonia charging mass percentage was 88%.
[0078] Table 1. Summary of experimental conditions and results for each embodiment and comparative example. Based on Examples 1, 2, 4, and Comparative Example 2, the preferred temperature range for high-temperature heat treatment of raw vermiculite is 800℃-1200℃. As the heat treatment temperature increases, the percentage of ammonia mass charged first increases and then decreases within the same effective ammonia charging time; in other words, the effective ammonia charging time required to achieve the same percentage of ammonia mass charged first shortens and then lengthens. Within the suitable temperature range, the bound water and free water between the vermiculite layers are gradually removed as the temperature rises. The layers expand under heat, forming a well-developed porous structure, and the specific surface area and porosity of the material increase simultaneously. This not only widens the mass transfer and diffusion channels for ammonia but also provides more physical adsorption sites, thus accelerating the ammonia charging rate, shortening the effective ammonia charging time, and simultaneously increasing the percentage of ammonia mass charged. When the temperature exceeds the optimal value, the vermiculite undergoes excessive expansion, the layered structure collapses and breaks, and some pores sinter and close, leading to a decrease in effective porosity and obstruction of mass transfer paths. Ultimately, this manifests as a slower ammonia charging rate, a longer effective ammonia charging time, and a decrease in the percentage of ammonia mass charged.
[0079] Based on Examples 2, 3, and 4, the optimal heat treatment holding time is 30-240 min. With prolonged holding time, the percentage of ammonia mass initially increases and then decreases. Extended holding time allows for more thorough heating of the vermiculite, more complete removal of interlayer moisture, and more complete expansion development. This gradually increases the material's specific surface area and porosity, providing more adsorption sites and more unobstructed diffusion channels for ammonia. Therefore, the ammonia mass transfer efficiency is improved, the effective ammonia filling time is shortened, and the percentage of ammonia mass increases accordingly. However, if the holding time is too long, the vermiculite sheets are exposed to high temperatures for an extended period, leading to decreased structural stability and a tendency for sheet sintering and pore structure collapse. This reduces the effective pore volume and adsorption sites, hindering ammonia diffusion and adsorption, resulting in a decrease in the ammonia filling rate, a prolonged effective ammonia filling time, and a decline in the percentage of ammonia mass.
[0080] Based on Examples 2, 6, and 7, the preferred aging time is 20-100 min. With prolonged impregnation time, the percentage of ammonia mass charge first increases and then decreases within the same effective ammonia charging time. Within a suitable impregnation time range, with prolonged impregnation time, strontium chloride can more fully penetrate the pores and interlamellae of expanded vermiculite, resulting in a more uniform loading of active components, effective exposure of more ammonia adsorption active sites, and optimization of the pore structure. This improves both the ammonia adsorption capacity and the ammonia mass transfer adsorption rate, manifested as an increase in the percentage of ammonia mass charge and a shortening of the effective ammonia charging time. When the impregnation time is too long, the active component load reaches saturation and excessive accumulation occurs, clogging the internal pores of the vermiculite, causing a decrease in material porosity and specific surface area, increasing the resistance to ammonia diffusion and mass transfer, ultimately leading to a decrease in ammonia mass transfer efficiency, a prolonged effective ammonia charging time, and difficulty in further increasing the percentage of ammonia mass charge, which may even decrease.
[0081] Based on Examples 2, 8, 5, and 8, the preferred EVMT / SrCl2 mass ratio is 0.5:10-3.5:10. This ratio plays a dominant regulatory role in ammonia charging performance, directly determining the total number of adsorption sites and the pore mass transfer structure. As the proportion of EVMT carrier gradually increases, the percentage of ammonia charging mass first increases and then decreases within the same effective ammonia charging time. When the carrier ratio is too low, there is insufficient porous carrier to provide mass transfer channels, the ammonia diffusion path is blocked, and it is difficult to fully contact the internal active components, resulting in a slow ammonia charging rate and a long effective ammonia charging time. At the same time, the active components cannot fully exert their adsorption effect, and the ammonia charging mass percentage is low. As the carrier ratio increases, the porous carrier provides more mass transfer channels and a more dispersed framework, the dispersion of active components is improved, and adsorption sites are effectively exposed. This not only accelerates the ammonia mass transfer rate and shortens the effective ammonia charging time, but also increases the overall ammonia charging capacity and the ammonia charging mass percentage. However, when the carrier ratio is too high, the proportion of SrCl2 active components per unit mass of composite material decreases significantly, and the total number of chemical adsorption active sites is insufficient. Although there are sufficient mass transfer channels, the overall adsorption capacity is limited, ultimately leading to a significant decrease in the ammonia charging mass percentage. At the same time, due to the decrease in the density of active sites, the ammonia charging rate is slowed down to some extent, and the effective ammonia charging time is prolonged.
[0082] As described above, this invention provides a SrCl2 / EVMT composite material and its preparation method. Expanded vermiculite, which is abundant, inexpensive, and possesses a multi-level porous structure, is selected as the carrier. A solution impregnation method, characterized by mild conditions, simple operation, and no complex post-treatment steps, is employed to achieve uniform loading of the SrCl2 active component within the carrier pores. Utilizing the pore confinement effect of the expanded vermiculite matrix, the severe volume expansion during the SrCl2 ammoniation-deammoniation process is mitigated, inhibiting material agglomeration and pulverization, as well as the volatilization and loss of active salts, thus improving ammonia mass transfer conditions and synergistically enhancing the ammonia adsorption efficiency and cycle stability of the composite material. This invention significantly reduces raw material costs and production process barriers while ensuring ammonia storage performance, and the process is easily scaled up for industrial applications. The prepared composite material is suitable for the actual operating conditions of on-board solid-state ammonia SCR systems, effectively reducing NO2 emissions from vehicle exhaust. x This will provide a safe and reliable solid ammonia source and promote the industrialization of solid ammonia storage technology.
[0083] Although the invention has been described with reference to illustrative embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that elements of the described embodiments can be substituted with substantially equivalents. Furthermore, many modifications can be made without departing from the scope of the invention to adapt particular situations or materials to the teachings of the invention. Therefore, this document is not intended to limit the invention to the specific embodiments disclosed for carrying out the invention, but rather to include all embodiments falling within the scope of the appended claims.
Claims
1. A method for preparing a strontium chloride / expanded vermiculite composite ammonia storage material, characterized in that, include: Provide expanded vermiculite with a multi-level pore structure; Expanded vermiculite was mixed and stirred with strontium chloride aqueous solution to obtain a mixed slurry, which was then allowed to stand and age. The mixed slurry was dried to obtain a strontium chloride / expanded vermiculite composite ammonia storage material.
2. The preparation method according to claim 1, characterized in that, The preparation steps of the expanded vermiculite include: The raw vermiculite is heated to a preset temperature, kept at that temperature, and then allowed to cool naturally.
3. The preparation method according to claim 2, characterized in that, The preset temperature is 800℃-1200℃.
4. The preparation method according to claim 2, characterized in that, The heat preservation time is 30min-240min.
5. The preparation method according to claim 1, characterized in that, The mass ratio of the expanded vermiculite to the strontium chloride in the strontium chloride aqueous solution is 0.5:10-3.5:
10.
6. The preparation method according to claim 1, characterized in that: The static aging time is 20-100 minutes.
7. A strontium chloride / expanded vermiculite composite ammonia storage material, characterized in that: It is prepared by the preparation method of strontium chloride / expanded vermiculite composite ammonia storage material according to any one of claims 1-6. The strontium chloride / expanded vermiculite composite ammonia storage material includes: an expanded vermiculite matrix with a multi-level porous structure as a carrier, and strontium chloride, an active adsorbent component uniformly loaded on the expanded vermiculite matrix.
8. The use of the strontium chloride / expanded vermiculite composite ammonia storage material according to claim 7 in an on-board solid ammonia SCR system.
9. An ammonia storage material for SCR denitrification of motor vehicle exhaust, characterized in that, The ammonia storage material comprises the strontium chloride / expanded vermiculite composite ammonia storage material as described in claim 7; the ammonia storage material provides a reducing agent for the tail gas denitrification reaction by adsorbing, storing, and controlling the release of ammonia gas.
10. NO in a type of motor vehicle exhaust x The selective catalytic reduction removal method is characterized by, Includes the following steps: (1) Adsorption of ammonia: First, place the strontium chloride / expanded vermiculite composite ammonia storage material as described in claim 7 in an ammonia atmosphere to allow the material to adsorb ammonia and obtain a pre-ammonia storage material; (2) Denitrification reaction: The pre-stored ammonia material is placed in the exhaust gas passage of the motor vehicle. Under the conditions of SCR catalyst and exhaust gas temperature, the ammonia released by the material reacts with NO and NO2 in the exhaust gas to generate N2 and H2O, thereby achieving NO denitrification. x Remove.
